Regulation of New Drug Approval in Taiwan. (September 2016) - Yang, Ya-Ting; Huang, Hsiau-Wen; Chen, Ya-Ting; Chiang, Yu-Mei; Tzou, Meir-Chyun
Taiwan Food and Drug Administration (TFDA) was established in 2010 as the nation's principal consumer product protection agency of food, drugs, medical devices, and cosmetics. By integrating 4 agencies (the Bureau of Food Safety, Bureau of Pharmaceutical Affairs, Bureau of Food and Drug Analysis, and Bureau of Controlled Drugs), TFDA holds the mission of protecting and promoting the public health through regulation modernization to enhance the availability of safe medical products and foods. To address the unmet medical needs and public health, TFDA has utilized regulatory science to evaluate review principles and risk management to properly oversee the overall life cycle of medicinal products. A lot of measures have been accomplished to build an efficient, transparent, and internationally harmonized regulatory system. With the first-in-the-world new drug afatinib approved in Taiwan, TFDA has successfully built up capacity and capability in the review and approval of new drugs. This article summarizes the efforts TFDA has been making in the domain of medicinal product management, highlighting policies and strategies for the future.